PERKEMBANGAN KOMERSIALISASI PERTANIAN DI INDONESIA DAN PROYEKSINYA 2005-2050 - Saparita, Rachmini (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2005)
This article identified the growth commercial agriculture through diversification of crops to predict the process of agricultural transformation in Indonesia. The result showed that the growth of commercial agriculture was varied. Some provinces, such as Jakarta, West Java, North and West Sumatera, Riau, Kalimantan, Midle and South Sulawesi, which had low index, commercialization worked well. The economic pattern of their farmer changed from subsistence to commercial. Agricultural development in those provinces entered to the growth and advanced stages of agricultural transformation. However, others provinces, which had high index, commercial agriculture worked poorly. For all provinces outside Java islands, the cause of those high indexes were predicted by several factors, such as lack of infrastructure, remote areas, and other limitations, so that business accesses to outside areas were not run well. For all provinces inside Java islands, the cause was predicted by the excessive of subsistence agriculture, so that commercial agriculture was delayed, while other areas were suited for various food crops type. From that situation it could be concluded that agricultural development was not spread equally for every province in Indonesia. Since agricultural development policies were such as the existing strategies, the growth of commercial agriculture were predicted would not affect the increase of farmer’s income, because the growth was not caused by transformation of agricultural economic pattern from subsistence to commercial, but was caused by agriculture household enlargement. Consequently, the government should apply land reform policy immediately.